Sexual Inversion - Ellis, H. author. aut Link
VII, 351 p.
Keywords: Sexual Inversion was the first English medical textbook about homosexuality. It had a chequered publishing history, going through five editions between 1896 and 1915. This edition, with a long critical introduction, places the book in its intellectual and social contexts, and considers the historiography surrounding this important work.